Outdoor daylight exposure and longer sleep promote wellbeing under COVID‐19 mandated restrictions. (21st September 2021) - Korman, Maria; Tkachev, Vadim; Reis, Cátia; Komada, Yoko; Kitamura, Shingo; Gubin, Denis; Kumar, Vinod; Roenneberg, Till
Summary: Light is an important regulator of daily human physiology in providing time‐of‐day information for the circadian clock to stay synchronised with the 24‐hr day. The coronavirus disease 2019 (COVID‐19) pandemic led to social restrictions in many countries to prevent virus spreading, restrictions that dramatically altered daily routines and limited outdoor daylight exposure. We previously reported that sleep duration increased, social jetlag decreased, and mid‐sleep times delayed during social restrictions (Global Chrono Corona Survey, N  = 7, 517). In the present study, we investigated in the same dataset changes in wellbeing and their link to outdoor daylight exposure, and sleep–wake behaviour. In social restrictions, median values of sleep quality, quality of life, physical activity and productivity deteriorated, while screen time increased, and outdoor daylight exposure was reduced by ~58%. Yet, many survey participants also reported no changes or even improvements. Larger reductions in outdoor daylight exposure were linked to deteriorations in wellbeing and delayed mid‐sleep times. Notably, sleep duration was not associated with outdoor daylight exposure loss. Longer sleep and decreased alarm‐clock use dose‐dependently correlated with changes in sleep quality and quality of life. Regression analysis for each wellbeing aspect showed that a model with six predictors including both levels and their deltas of outdoor daylight exposure, sleep duration and mid‐sleep timing explained 5%–10% of the variance in changes of wellbeing scores (except for productivity). As exposure to daylight may extenuate the negative effects of social restriction and prevent sleep disruption, public strategies during pandemics should actively foster spending more daytime outdoors.